2011
DOI: 10.1007/s00787-011-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of substance use in adolescents attending a mental health department

Abstract: Objective: To describe patterns of substance use in adolescents initiating mental health treatment, and to analyse factors associated to a high risk pattern of substance use differentially by gender. Methods:Two hundred and thirty seven 12-to 17-year-old new patients in an urban public mental health service were prospectively recruited and evaluated using semi-structured interviews and standardized questionnaires to obtain socio-demographic, psychopathological, family, school and substance use data. Results:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
3
5
0
2
Order By: Relevance
“…Adolescents with co-occurring SU and psychiatric problems are now commonly understood to be the rule rather than the exception [32, 33], and psychiatric comorbidities complicate treatment and can result in poorer outcomes [34]. SU treatment samples typically show higher rates of conduct disorder, oppositional defiant disorder, attention deficit hyperactivity disorder, depression, anxiety, post-traumatic stress disorder, and borderline personality than community samples [35, 36].…”
Section: Su and Adolescent Healthmentioning
confidence: 99%
“…Adolescents with co-occurring SU and psychiatric problems are now commonly understood to be the rule rather than the exception [32, 33], and psychiatric comorbidities complicate treatment and can result in poorer outcomes [34]. SU treatment samples typically show higher rates of conduct disorder, oppositional defiant disorder, attention deficit hyperactivity disorder, depression, anxiety, post-traumatic stress disorder, and borderline personality than community samples [35, 36].…”
Section: Su and Adolescent Healthmentioning
confidence: 99%
“…Como se esperaba, la presencia más frecuentemente hallada en el grupo de patología dual era de un trastorno externalizante y el consumo abusivo de cannabis (Díaz et al, 2011). Es más, este grupo mostró una frecuencia más alta de visitas involuntarias (llegada mediante ambulancia) y una tasa más alta de ingreso a unidades asistenciales ambulatorias, en comparación con el grupo de trastorno psiquiátrico.…”
Section: Discussionunclassified
“…On the other hand, the Negative Emotionality scale showed some interesting associations mainly with higher use of other type of drugs, which highlights the importance of internalizing symptoms (Hussong et al, 2011), and negative emotionality (Elkins et al, 2006) in the development of SUD in adolescents. Previous studies have reported a high prevalence of psychiatric comorbidity among adolescent patients with SUD (Couwenbergh et al, 2006; Hawkins, 2009; Magallón-Neri et al, 2012), mainly in combination with conduct disorder and other disruptive behavior disorders (Hawkins, 2009), but it is also relevant with affective disorders, specially in girls, as suggested by Díaz et al (2011).…”
Section: Discussionmentioning
confidence: 99%